An analysis of population genetic differentiation and genotype–phenotype association across the hybrid zone of carrion and hooded crows using microsatellites and MC1R - FREDRIK HAAS; MARIE A. POINTER; NICOLA SAINO; ANDERS BRODIN; NICHOLAS I. MUNDY; BENGT HANSSON (Molecular Ecology, 2009)
The all black carrion crow ( Corvus corone corone ) and the grey and black hooded crow ( Corvus corone cornix ) meet in a narrow hybrid zone across Europe. To evaluate the degree of genetic differentiation over the hybrid zone, we genotyped crows from the centre and edges of the zone, and from allopatric populations in northern (Scotland–Denmark–Sweden) and southern Europe (western–central northern Italy), at 18 microsatellites and at a plumage candidate gene, the MC1R gene. Allopatric and edge populations were significantly differentiated on microsatellites, and populations were isolated by distance over the hybrid zone in Italy. Single‐locus analyses showed that one locus, CmeH9, differentiated populations on different sides of the zone at the same time as showing only weak separation of populations on the same side of the zone. Within the hybrid zone there was no differentiation of phenotypes at CmeH9 or at the set of microsatellites, no excess of heterozygotes among hybrids and low levels of linkage disequilibrium between markers. We did not detect any association between phenotypes and nucleotide variation at MC1R , and the two most common haplotypes occurred in very similar frequencies in carrion and hooded crows. That we found a similar degree of genetic differentiation between allopatric and edge populations irrespectively of their location in relation to the hybrid zone, no differentiation between phenotypes within the hybrid zone, and neither heterozygote excess nor consistent linkage disequilibrium in the hybrid zone, is striking considering that carrion and hooded crows are phenotypically distinct and sometimes recognised as separate species.